1062 Hypnotic Use in Insomnia Clinic Following Direct-to-patient Education Tool. (27th April 2018) - Chan, L C; Martin, J L; Lau, M K; Smith, J; Fung, C H
Abstract: Introduction: The use of hypnotics has been associated with increased risk of falls, cognitive impairment, and loss in quality of life in older adults. Discontinuation or dose reduction of benzodiazepines occurs more frequently in patients who receive direct-to-consumer education about the risks and benefits of hypnotics. At our medical center, a direct-to-consumer education quality improvement program targeting older adults on hypnotics has been ongoing. We present results from a quality improvement project that assesses rates of hypnotic discontinuation in veterans attending insomnia clinic among those considered for the direct-to consumer mailings. Methods: Patients who had at least one visit in the insomnia clinic at a VA medical center between January 2015 and October 2017 and who had been flagged as a candidate for the ongoing direct-to-consumer program for hypnotics (i.e., age ≥ 65 years with 60 day supply or greater of benzodiazepines [z-drugs also considered in fiscal year 2016] and no schizophrenia, spinal cord injury, seizure disorder, or palliative care) were considered for the analysis. Hypnotic use was assessed at a single time point in October 2017. We used a two-sample test of proportions to compare sedative hypnotic medication use based upon VA pharmacy data for patients who received and who did not receive the mailing. Results: A total of 24 patients were eligible to receive the direct-to-consumer mailing, and 12 patients were mailed the information on hypnotics. A larger proportion of patients who received the mailing are no longer on benzodiazepines or nonbenzodiazepine hypnotic medications compared to patients who did not receive the mailing (58% versus 8.3%, p=.01). Conclusion: Our results are consistent with previous findings that direct-to-patient education tools can reduce the use of hypnotics. To improve the quality of patient care, more older veterans in our insomnia clinic who are using hypnotics should receive the direct-to-consumer mailing. Support (If Any): VAGLA GRECC; NIAK23AG045937.